Seed Quality Description of Kilemo (Litsea cubeba (Lour.) Pers.) - Eliya Suita; Hani Sitti Nuroniah; Abdul Hakim Lukman; Danu; Deddy Dwi Nur Cahyono; Aam Aminah; Dida Syamsuwida; Nurhasybi; Darwo; Atfi Indriany Putri; Supatmi (Forest and Nature, 2025)
Kilemo (Litsea cubeba (Lour.) Pers.), a forest tree species of the Lauraceae family, is naturally distributed in China, Taiwan, and Southeast Asia, including Indonesia. This species is valued for its high-quality essential oils and its potential applications in the biopharmaceutical and chemical industries. However, the semi-recalcitrant nature of kilemo seeds presents challenges in storage and germination, necessitating research to optimize seed quality and propagation methods. This study aims to evaluate the physical and physiological qualities of kilemo seeds sourced from highland regions in West Java and North Sumatra and to determine the best pretreatment methods to enhance germination performance. Seed samples were collected from Ciwidey, Mount Papandayan (West Java), and Aek Nauli (North Sumatra). The study assessed seed moisture content, purity, 1,000-seed weight, and seed viability. Different soaking treatments (plain water, boron solutions, KNO3 solutions, and coconut water) were applied, followed by germination tests under two sowing conditions: open seedbeds and plastic-covered seedbeds. The results indicate that kilemo seeds exhibit moisture content ranging from 13.01% to 14.68%, purity above 96.77%, and a weight of 1,000 seeds varying from 21.36 to 27.86 g. Germination trials revealed that seeds soaked in 100% coconut water for 3 or 6 hours exhibited the highest germination percentages and vigor, particularly in an open seedbed condition. These findings suggest that coconut water pretreatment enhances seed germination and viability, offering an effective method for improving the propagation success of kilemo. The study provides valuable insights into optimizing seed handling techniques to support the conservation and commercial cultivation of this species.